2020
DOI: 10.1038/s41467-020-18412-w
|View full text |Cite|
|
Sign up to set email alerts
|

Time-restricted feeding alters lipid and amino acid metabolite rhythmicity without perturbing clock gene expression

Abstract: Time-restricted feeding (TRF) improves metabolism independent of dietary macronutrient composition or energy restriction. To elucidate mechanisms underpinning the effects of short-term TRF, we investigated skeletal muscle and serum metabolic and transcriptomic profiles from 11 men with overweight/obesity after TRF (8 h day−1) and extended feeding (EXF, 15 h day−1) in a randomised cross-over design (trial registration: ACTRN12617000165381). Here we show that muscle core clock gene expression was similar after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 55 publications
(79 reference statements)
2
92
1
1
Order By: Relevance
“…A reduction in reported energy intake was expected due to previous reports suggesting there may be up to 20% energy reduction in longer-term (10)(11)(12)(13)(14)(15)(16) week) TRE interventions [1][2][3][4]. However, the consistency in energy intake between the habitual and intervention periods in the current study suggests participants did not make substantial or additional dietary changes other than reducing the time window of eating and is reflected in the lack of change to physiological measures such as body mass.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A reduction in reported energy intake was expected due to previous reports suggesting there may be up to 20% energy reduction in longer-term (10)(11)(12)(13)(14)(15)(16) week) TRE interventions [1][2][3][4]. However, the consistency in energy intake between the habitual and intervention periods in the current study suggests participants did not make substantial or additional dietary changes other than reducing the time window of eating and is reflected in the lack of change to physiological measures such as body mass.…”
Section: Discussionmentioning
confidence: 49%
“…Controlled studies of isoenergetic TRE have shown beneficial effects on glucose tolerance, insulin sensitivity, and 24-h glucose profiles in individuals at risk of developing type 2 diabetes mellitus (T2D) [7][8][9] as well as reductions in appetite in persons with overweight/obesity [10]. The proposed mechanism for improved metabolic health with TRE, despite no restriction in energy intake, is temporal alignment between energy consumption and normal diurnal rhythms of hormones involved in metabolic processes and energy regulation [11][12][13]. For individuals with T2D, diurnal regulation of glucose is altered such that highest peaks in glucose occur in the morning [14], compared to in the afternoon/evening in those with normoglycemia [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were some missing measurement, but each participant had 4 ∼ 6 measurement, resulting in a total of 63 samples in restricted group and 62 samples in unrestricted group. Detailed description of this study has been previously published [35]. This RNA-seq dataset is publicly available in GEO (GES129843).…”
Section: Real Data Applicationsmentioning
confidence: 99%
“…Indeed, TRF increased the skeletal muscle uptake of glucose and branchedchain amino acids (BCAAs) (Jones et al, 2020). The effects of TRF in men who are overweight/obese have been elucidated using the circadian transcriptome of skeletal muscle (Lundell et al, 2020). TRF conducted for 8 h stimulated rhythmicity of amino acid metabolites and its transporter expression without perturbing the expression of molecular clock genes (Lundell et al, 2020).…”
Section: Therapeutic Potential Of Chrono-nutrition Against Are-related Muscle Dysfunctionsmentioning
confidence: 99%